Health and productivity of trypanotolerant and susceptible cattle exposed to trypanosomiasis in Gabon and the impact of strategic chemoprophylaxis - Ordner, G.; Colardelle, C.; D'Ieteren, G.D.M.; Dumont, P.; Itty, P.; Jeannin, P.; Leak, S.G.A.; Maehl, J.H.H.; Nagda, S.M.; Paling, R.W.; Rarieya, J.M.; Thorpe, W.R.; et al. (ILCA/ILRAD, 1988)
Studies the health and performance of two strains trypanotolerant N'Dama cattle, susceptible Nguni cattle and their crosses over a three-year period, 1983-1985, at OGAPROV ranch in Gabon; presents the influences of breed and animal age on the prevolence, species and intensity of trypanosome parasitaemia; and estimates the effects of trypanosome infection and breed and cow locatational status on the {PCV and reproductive performance.